PENGELOLAAN KEGIATAN EKSTRAKURIKULER OLAHRAGA DI SD/MI/SEDERAJAT DI WILAYAH KERJA KABUPATEN KULONPROGO YOGYAKARTA TAHUN 2015 - Nurcahyo, Fathan; Hermawan, Hedi Ardiyanto (Jurnal Pendidikan Jasmani Indonesia, 2017)
Abstract The implementation of sport extracurricular activities in some elementary schools located in the working area of Kulonprogo Regency has not been properly managed. This study intends to determine the management system of sport extracurricular activities in SD / MI / equal (elementary school) in the working area of Kulonprogo Regency, Yogyakarta in 2015. This research was qualitative-quantitative descriptive research. The method used in this research was by survey method with instrument and data collection technique using open questionnaire. The research subjects were all teachers of PJOK (Physical Education) in elementary school in the working area of Kulonprogo Regency, Yogyakarta in 2015 who was studying undergraduate bachelor degree (S1 PKS PJKR) in UNY. The data analysis technique in this research was done by using qualitative-quantitative descriptive statistical analysis technique with percentage. The result of the research shows that from 50 PJOK teachers from 50 elementary schools in Kulonprogo Regency, Yogyakarta, in details, 48 teachers in school (96%) of schools have implemented the management and development of sport extracurricular activities well and only 2 (4%) Schools that have not. Abstrak Pelaksanaan kegiatan ekstrakurikuler olahraga di beberapa sekolah dasar yang berada di wilayah kerja Kabupaten Kulonprogo belum dikelola dengan tepat. Penelitian ini bertujuan untuk mengetahui sistem pengelolaan kegiatan ekstrakurikuler olahraga di SD/MI/sederajat di wilayah kerja Kabupaten Kulonprogo, Yogyakarta pada tahun 2015. Penelitian ini merupakan penelitian deskriptif kualitatif-kuantitatif. Metode yang digunakan dalam penelitian ini adalah metode survei dengan instrumen dan teknik pengumpulan data menggunakan angket terbuka. Subjek dalam penelitian ini adalah seluruh guru PJOK SD/MI/sederajat di wilayah kerja Kabupaten Kulonprogo, Yogyakarta pada tahun 2015 yang sedang menempuh studi sarjana (S1 PKS PJKR) di UNY. Teknik analisis data dalam penelitian ini menggunakan teknik analisis statistik deskriptif kualitatif-kuantitatif dengan persentase. Hasil penelitian menunjukkan bahwa dari 50 orang guru PJOK dari 50 sekolah SD/MI/sederajat di wilayah kerja Kabuupaten Kulonprogo, Yogyakarta secara rinci ada 48 (96%) sekolah telah melaksanakan pengelolaan dan pengembangan kegiatan ekstrakurikuler olahraga dengan baik dan hanya 2 (4%) sekolah saja yang belum. Kata kunci: Pengelolaan, Kegiatan Ekstrakurikuler Olahraga, SD/MI/sederajat.